Clinical Profile of Febrile Neutropenia in Children with Malignancies in a Tertiary Care Hospital: A Prospective Observational Study - Mariam, Ayesha; Hegde, Niranjan Gurunath; Srinivasan, Arathi; Thangadorai, Ravikumar (Indian Journal of Medical and Paediatric Oncology, 2024)
Introduction Febrile neutropenia is a dreadful complication associated with malignancies. Knowledge of locally prevalent pathogens and their resistance pattern is of paramount importance in guiding antimicrobial therapy.Objectives The aim of the study was to identify the common infectious agent, antibiotic susceptibility of culture positive patients, and outcomeMaterials and Methods We conducted a single-center prospective observational study. Forty-three children with febrile neutropenia episodes admitted in KKCTH, Chennai, were included in the study. The duration of the study was 1 year. Relevant patient and disease specific details were obtained, results were analyzed, and conclusions were drawn.Results There were 90 episodes of febrile neutropenia. Overall culture positivity was identified in 37 cases (41.11%). Bacteremia (23.3%) was the most common cause of microbiologically documented infection. Gram-positive organisms (60%) were more commonly documented. Among the gram-positive organisms, coagulase-negative Staphylococcus aureus was the predominant isolate followed by Streptococcus. Central line–associated bloodstream infections were documented in 13.33%. Chemo-port removal was done in four children. Three had invasive fungal disease. The majority of the gram-negative isolates were resistant strains. Morbidity was significantly more in gram-negative infections. Overall outcome was good though three children succumbed to sepsis.Conclusion A vigilant management of illness is essential. Chemo-port carries risk of severe infection. Protocol-based management of catheter-related bloodstream infection (CRBSI) can limit the number of chemo-port removal. Though gram-positive organisms are in the rise, gram-negative organisms are still responsible for significant morbidity. Early initiation of broad-spectrum empirical antibiotics with optimal gram-positive coverage is crucial. Children with suspected fungal infections should be aggressively evaluated and treated. An organized approach is the key in successful management.
Keywords: acute lymphoblastic leukemia; CRBSI; microbiologically documented infection; invasive fungal disease; gram-negative organism